Sistem Pendukung Keputusan Menggunakan Metode SAW dan TOPSIS untuk Memutuskan Penerima Reward Karyawan Terbaik di McD Pancing - Putri, Cindy Ananda; Hasugian, Abdul Halim (Program Studi Teknik Informatika Universitas Pamulang, 2024)
In every industry or institution, there will definitely be a reward in the form of income for employees as compensation for the work they have done. Apart from giving out main income rewards to employees, each industry or institution often gives out rewards in addition to main income to encourage the productivity and abilities of its employees. The rewards given to McD Pancing employees are in additional form and will be given outside of their main income. Evaluation of employee abilities is based on benchmarks that have been established by the institution. However, currently the system of giving rewards to McD Pancing employees has various shortcomings, such as giving rewards which are being tried based on individual analysis and the assessment is still individual, not transparent, less efficient and there is little precision or accuracy in giving rewards. To help select McD Pancing employees who are competent to receive rewards appropriately and carefully and respond to problems that arise, a Decision Support System (DSS) is needed as a solution to these cases. The expertise of the system for collecting decisions uses methods that have been created so that it is hoped that the assessment method will be much more accurate, efficient and efficient using the TOPSIS and SAW methods. The TOPSIS method is based on the design that the best filtered substitute not only has the shortest distance from the positive perfect solution but also has the longest distance from the minus perfect solution. Based on the results of this research, it is proven that employees who receive rewards as the best employees according to the SAW and TOPSIS method calculations are determined by employees with SAW calculation results of 87.06 and TOPSIS calculation results of 0.679 and mixed results of 43.89.